PENINGKATAN HASIL BELAJAR IPA DENGAN MODEL CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS IV SD NEGERI GUNTURMADU - Sukino Sukino (PGSD FKIP UPR, 2023)
This study aims to improve student learning outcomes in grades IV-A SD N Gunturmadu in science learning using the CTL learning model. This research is classroom action research. The design of this study used the Kemmis & Mc Taggart model. The research subjects in this study were class IV-A SD N Gunturmadu with a total of 21 students and carried out in 2 cycles. The data collection instrument is a test to measure student learning outcomes. The average value in the first cycle is 75.33 with a total percentage of 62% and in the second cycle has an average of 88.00 and a percentage of 100%.